2016
DOI: 10.1002/ajpa.22959
|View full text |Cite
|
Sign up to set email alerts
|

Population inference from contemporaryAmerican craniometrics

Abstract: Population inference methods that allow for the model-bound estimation of admixture and ancestry proportions from craniometric data not only enable parallel-skeletal and genetic-analyses but they are also shown to be more informative than those methods that perform hard classifications using externally-imposed categories or seek to explain gross variation by low-dimensional projections. Am J Phys Anthropol 160:604-624, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 103 publications
(147 reference statements)
0
35
0
Order By: Relevance
“…To determine whether there exists a relationship between the nature of the FD3 misclassifications (the reference groups to which targets are assigned) and individual levels of continental—African, European, and Indigenous American—ancestry, we generated for all PCOME test samples their relative proportions, or percent, of African, European, and Indigenous American ancestry. These estimates were derived from traditional cranial measurement data following the procedures already described by Algee‐Hewitt for the inference of continental ancestry and the quantification of admixture among contemporary individuals of United States and Latin American origins at various geographic (country‐wide, regional, and state) scales. We applied the unsupervised model‐based clustering methods of finite mixture analysis to a matrix of 20 craniofacial shape measures for a sample of 2277 individuals.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To determine whether there exists a relationship between the nature of the FD3 misclassifications (the reference groups to which targets are assigned) and individual levels of continental—African, European, and Indigenous American—ancestry, we generated for all PCOME test samples their relative proportions, or percent, of African, European, and Indigenous American ancestry. These estimates were derived from traditional cranial measurement data following the procedures already described by Algee‐Hewitt for the inference of continental ancestry and the quantification of admixture among contemporary individuals of United States and Latin American origins at various geographic (country‐wide, regional, and state) scales. We applied the unsupervised model‐based clustering methods of finite mixture analysis to a matrix of 20 craniofacial shape measures for a sample of 2277 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…We applied the unsupervised model‐based clustering methods of finite mixture analysis to a matrix of 20 craniofacial shape measures for a sample of 2277 individuals. This large, mixed‐sex and multipopulation sample was formed from the combination of (i) the PCOME test cases described above and (ii) the subset of forensic and skeletal research cases from the Forensic Data Bank (FDB) reported in previous studies by Algee‐Hewitt . These FDB cases represent individuals of self‐reported or ascribed Black, Hispanic, Native American, or White identity.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations